Endovascular treatment in cerebrovascular pathologies at the Instituto de Previsión Social from 2016 to 2019. - Castro-Florentín, Javier Aníbal; Britez-Barrios, Edulfo; Jara-Verón, Juan José (Medicina Clínica y Social, 2023)
Introduction: Cerebrovascular diseases are all diseases in which the blood vessels of the brain are mainly involved. Objective: To determine the frequency of endovascular treatments for cerebrovascular pathologies at the Instituto de Previsión Social to provide an epidemiological overview and an approach to endovascular treatment. Method: This was an observational, descriptive, temporally retrospective, and cross-sectional study. Sampling was performed using a simple random probabilistic method. Sociodemographic variables: sex and age. Clinical data: amphiographic findings, reason for consultation, diagnosis, treatment, and comorbidities. Results: The frequency of endovascular treatment for cerebrovascular pathology was 47.08%. In total, 113 patients were included in the study, most of whom were women. The average age of the patients was 56 years, and the most frequent age was 64 years. The most frequent findings were cerebral arteriovenous malformations, normal angiography findings, and aneurysms. The most frequent reasons for consultation were headaches, neurological deficits, sensory disturbances, and seizures. Discussion: These findings coincide with the literature in this regard and contribute to the epidemiological profile of this group of pathologies.
Keywords: endovascular; cerebrovascular; treatment